Die Pestarztmaske im Deutschen Medizinhistorischen Museum Ingolstadt - Ruisinger, Marion (NTM Zeitschrift für Geschichte der Wissenschaften, Technik und Medizin, 2020)
This paper is part of Forum COVID-19: Perspectives in the Humanities and Social Sciences. The figure of the plague doctor with the beak mask has become the symbol of the plague par excellence. It’s little wonder that the plague mask in the collection of the German Museum of the History of Medicine in Ingolstadt (Bavaria) is one of the museum’s most popular objects and motifs. This forum paper investigates the figure of the plague doctor on several levels: first, it analyses contemporary textual and image sources in regard to protective clothing used in times of plague and the respective role of the beak-like part of the mask. Then it takes a close look at the Ingolstadt specimen. By examining the mask’s materiality and fabrication, questions of its authenticity and practicability are raised. Finally, the Ingolstadt mask is compared with the specimen at the German Historical Museum in Berlin. The conclusion: the beak mask is not mentioned before the mid-seventeenth century, and then only in Italy and Southern France. There is no proof at all of its use during plague outbreaks in Middle Europe. And the specimens in Ingolstadt and Berlin? Both masks present details which suggest that they were not used as protective clothing at all. We do not know, however, if they were produced as replicas for historic reasons or as fakes for the modern art market.
CRIS-Team Scopus Importer:2020-06-02
Keywords: iconography; material culture; museology; plague mask; protective clothing

Observationes et Curationes Nurimbergenses: The Medical Practice of Johann Christoph Götz (1688-1733) - Kinzelbach, Annemarie; Grosser, Susanne; Jankrift, Kay Peter; Ruisinger, Marion (Clio Medica, 2016)
EVALuna2:33567

Trading Information The City of Nuremberg and the Birth of a Latin Medical Weekly - Kinzelbach, Annemarie; Ruisinger, Marion Maria (Civic Medicine. Physician, Polity, and Pen in Early Modern Europe, 2020)
This chapter analyses the founding of Commercium litterarium, among the earliest weekly medical journals (1731–1745), aiming to determine what was distinctive and significant about this journal in the history of knowledge and what made it possible. Commercium litterarium accelerated and regularized “knowledge in motion.” This is why such an enterprise was the undertaking of a society of medical officers in a major trading city. Nuremberg’s system and forms of commerce and communication enabled and inspired the creation of the journal. Equally important was that Nuremberg’s physicians were not only competing practitioners, but sworn civic doctors who comprised an organized community, a Collegium medicum, with a broad public mission. The public they strove to transform through their enterprise of gathering and reading, selecting and rewriting, translating vernacular into Latin and distributing was continuous with this local one, yet much wider: it was the medical and scientific Republic of Letters.<br
CRIS-Team WoS Importer:2021-08-13